(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Two types of PCM were investigated for use in phase change gypsum boards: salt hydrate and paraffin. The transition temperatures, or melting temperatures, of the PCM is near to standard or suggested room temperatures 20-21 °C for heating-dominated climates or 25-27 °C for cooling-dominated climates. Phase change gypsum boards were produced by using three different methods: simple immersion for 1 hour and direct incorporation of raw and microencapsulated PCMs in 5 and 10% of composition mass. PCM were tested and the effects of energy conservation of PCM gypsum boards were determined. Also some physical and mechanical properties were determined to investigate the effect of PCM addition to gypsum boards.